2007
DOI: 10.5897/ajb2007.000-2326
|View full text |Cite
|
Sign up to set email alerts
|

Paecilomyces fumosoroseus blastospore production using liquid culture in a bioreactor

Abstract: There are many advantages to using liquid cultures for the production of blastospores. These include mainly the processes of scale up which are relatively easy, as well as the control of parameters such as temperature, aeration and pH. In this work, we evaluated the production of Paecilomyces fumosoroseus blastospores using a low-cost liquid culture medium in a fermenter in comparison to a medium commonly used for this purpose, with regard to yield and viability of blastospores. The two media contained the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Mass production of these propagules is easier and can be achieved within a shorter period of time by shaking the inoculated liquid culture medium. 31) The C. fumosorosea concentration produced in liquid media was approximately 1.9×10 8 CFU mL −1 . This result is still within the range produced with Jackson, Paris, and Catroux media, which was 1.4-5.5×10 8 propagules mL −1 after 3×10 6 propagules mL −1 .…”
Section: Discussionmentioning
confidence: 97%
“…Mass production of these propagules is easier and can be achieved within a shorter period of time by shaking the inoculated liquid culture medium. 31) The C. fumosorosea concentration produced in liquid media was approximately 1.9×10 8 CFU mL −1 . This result is still within the range produced with Jackson, Paris, and Catroux media, which was 1.4-5.5×10 8 propagules mL −1 after 3×10 6 propagules mL −1 .…”
Section: Discussionmentioning
confidence: 97%
“…Blastospores of different entomopathogenic fungi, including Ifr have been used extensively in pest management programs on a worldwide scale (Avery 2002). Ifr blastospores easily can be mass produced in a shake-flask liquid culture medium (Jackson et al 1997(Jackson et al , 2003Lozano-Contreras et al 2007) and only require 6-8 h to germinate (Vega et al 1999). Considering that southern and central Florida experiences high humidity, it seems that the environmental conditions are conducive for the use of this fungal biopesticide as part of an IPM program in managing all stages of the psyllid population.…”
Section: Fdi Assessmentmentioning
confidence: 99%
“…Inch et al (1986) first reported that blastospores of I. farinosa and I. fumosorosea isolates could be produced in high numbers (1.19 x 10 8 blastospores ml -1 ) in 89 hours. Following this report, production of blastospores and submerged conidia of I. fumosorosea has been accomplished by 02 various workers (Shimizu and Aizawa, 1988;de la Torre and Cardenas-Cota, 1996;Jackson et al, 1997;Lozano-Contreras et al, 2007;Asaff et al, 2009;Kim et al, 2013). Blastospores, typically larger than aerial conidia and with thin cell walls are not amenable to simple drying techniques and tend to perish more rapidly during storage than conidia (Inch et al, 1986;Bidochka et al, 1987;Lane et al, 1991;Hegedus et al, 1992).…”
Section: Introductionmentioning
confidence: 99%